2011
DOI: 10.1371/journal.pone.0028986
|View full text |Cite
|
Sign up to set email alerts
|

RET Mutational Spectrum in Hirschsprung Disease: Evaluation of 601 Chinese Patients

Abstract: Rare (RVs) and common variants of the RET gene contribute to Hirschsprung disease (HSCR; congenital aganglionosis). While RET common variants are strongly associated with the commonest manifestation of the disease (males; short-segment aganglionosis; sporadic), rare coding sequence (CDS) variants are more frequently found in the lesser common and more severe forms of the disease (females; long/total colonic aganglionosis; familial).Here we present the screening for RVs in the RET CDS and intron/exon boundaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The combination of a de novo appearance and the fact that they are recurrent make it extremely likely that these variants are pathogenic even when no functional effects are found. 27 Common RET variants Several common variants (c.135G4A, c.1296 G4A, c.2307 T4G and c.2712C4G) were identified, for which the frequencies of those polymorphic alleles were similar to those described in other populations. 11,12,26 Garcia-Barcelo et al 28 showed that the haplotype containing three common RET variants (c.135G4A, c.1296G4A and c.2307 T4G) are represented in 66% of HSCR patients and c.1296G4 A is associated with a more severe form of HSCR.…”
Section: De Novo Ret Variantsmentioning
confidence: 64%
“…The combination of a de novo appearance and the fact that they are recurrent make it extremely likely that these variants are pathogenic even when no functional effects are found. 27 Common RET variants Several common variants (c.135G4A, c.1296 G4A, c.2307 T4G and c.2712C4G) were identified, for which the frequencies of those polymorphic alleles were similar to those described in other populations. 11,12,26 Garcia-Barcelo et al 28 showed that the haplotype containing three common RET variants (c.135G4A, c.1296G4A and c.2307 T4G) are represented in 66% of HSCR patients and c.1296G4 A is associated with a more severe form of HSCR.…”
Section: De Novo Ret Variantsmentioning
confidence: 64%
“…For the latter, the RET intron 1 SNP (rs2435357), highly associated with HSCR and known to interact with EDNRB [18] was also amplified and sequenced. Primers and PCR conditions are described elsewhere [22], [23], [24].…”
Section: Methodsmentioning
confidence: 99%
“…35 The paternally inherited RET variant c.3148C>T p.(Arg1050*) has previously been reported in a patient with Hirschsprung disease. 36 In mice, Slit2-Robo2 signaling is shown to restrict Gdnf-Ret signals to the site of the ureteric bud outgrowth preventing formation of multiple ureteric buds. Robo2 and Slit2 mice mutants show multiplex kidneys due to multiple ureteric bud formation.…”
Section: Variant In Ret (+164761)mentioning
confidence: 99%